Autism Spectrum Disorder in adults: an integrative review about strategies for promotion and maintenance of quality of life - Gabriela Garcia de Carvalho Laguna; Isadora Bagues Rodrigues; Sara Emanuelle dos Santos Neves; David Santos Libarino; Fernanda Beatriz Melo Maciel; Antônio Gonçalves Pessoa; Leticia Defensor da Silva Santos; Nilia Maria de Brito Lima Prado (São Paulo Medical Journal)
ABSTRACT BACKGROUND: People with Autism Spectrum Disorder (ASD) experience phases of life beyond childhood, which increase the difficulties inherent in each cycle. In contrast, the scientific literature lacks broad reviews of developmental strategies regarding quality of life, even though ASD encompasses changes in social, communicative, and behavioral skills. OBJECTIVE: This study aimed to identify strategies for promoting and maintaining quality of life among adults diagnosed with autism. DESIGN AND SETTING: This integrative review was conducted in Brazil. METHODS: This review searched the Scopus and Web of Science databases, from strategies that combined the descriptors ("Autism Spectrum Disorder"), ("Autism"), ("Aging"), and ("Quality of life"). Original studies with the full text available in English published between 2018 and 2023 were included, if they responded to the eligibility criteria. RESULTS: In total, 3,098 studies were identified, of which 44 were selected to compose the bibliographic sample of this review. The population sample included 184,653 participants diagnosed with ASD, aged on average 43.5 years old. The following were described for adults with autism: 1) cognitive aspects, 2) aspects related to suffering/mental illness, and 3) strategies to promote quality of life. CONCLUSION: This research contributes to basic clinical practice and promotes responsible care that attends to the health needs of people with autism throughout life. Early interventions in autistic adults and the availability of support throughout life are essential for maintaining cognitive health and quality of life.